Effects of Chitosan and Nano Titanium Dioxide on the Mechanical, Physicochemical and Antibacterial Properties of Corn Starch Films. Issue 8 (3rd August 2021) - Cheng, Long; Hao, Yanling; Song, Xiaoshuang; Chang, Qinglu
Abstract: Biodegradable composite films have been prepared from corn starch (CS) incorporating chitosan (CH) and nanoTiO2 by a solution casting method and the mechanical, physicochemical and antimicrobial properties of the films were determined. Scanning electron microscopy (SEM) observations demonstrated that the appropriate proportion of components resulted in ideally homogeneous surface of films. Fourier transform infrared (FTIR) spectra analysis revealed that hydrogen bonds were formed between CH and CS and a covalent interaction existed between the nanoTiO2 and the CS and CH. The addition of proper amounts of CH to a CS matrix produced an enhancement of mechanical and antimicrobial properties accompanied by lower water moisture resistance. Incorporation of nanoTiO2 into the CS/CH film increased the tensile strength, moisture resistance and impermeability to oil and achieved significant antimicrobial properties. The tensile strength of the nanoTiO2 /CH/CS composition film was 21.12 ± 0.34 MPa which was 6.27 times that of a plasticized CS film, while the antibacterial activity for Escherichia coli reached 94 ± 2%. The mechanical properties, moisture resistance and antimicrobial properties of the films were deteriorated by the incorporation of excessive nanoTiO2 because of self-aggregation of the nanoparticles.